New records of water mites (Acari: Hydrachnidia) from Brunei Darussalam, Borneo, with descriptions of two new species - Pešić, Vladimir; Chatterjee, Tapas; Marshall, David J.; Pavićević, Ana (Zootaxa, 2011)
New records of water mites (Acari: Hydrachnidia) from Brunei Darussalam are presented. Two new species are described: Hydrodroma bruneiensis (Hydrodromidae) and Litarachna bruneiensis (Pontarachnidae); Limnesia lembangensis Piersig, 1906 and Arrenurus bihamatus K. Viets, 1935, are reported for the first time from Brunei Darussalam. The water mite fauna of Borneo now tallies 41 species.